Detection of lard in butter using Raman spectroscopy combined with chemometrics. (1st December 2020) - Taylan, Osman; Cebi, Nur; Tahsin Yilmaz, Mustafa; Sagdic, Osman; Bakhsh, Ahmed Atef
Graphical abstract: Highlights: Demand exists for detection of lard in butter. A new Raman based method was developed for detection of lard in butter. Developed method has a great potential for discrimination of butter from adulterated samples. Developed method has a great potential for quantification of lard in butter (PCR and PLSR). Portable Raman based method could be easily adapted for control of butter in the field (industry). Abstract: There is a contentious need for robust and rapid methodologies for maintaining the authenticity of foods and food additives. The current paper presented a new Raman spectroscopy-based methodology for detection and quantification of lard in butter. Hierarchical cluster analysis (HCA) and principal component analysis (PCA) were successfully performed for the classification and discrimination of butter and lard-adulterated samples. Strong discrimination pattern was observed in the HCA analysis. Also, partial least squares regression and principal component regression ( R 2  = 0.99) were applied for quantification of lard in butter samples. Quite favorable prediction capabilities were observed in the cross-validation of PLS and PCR analysis for the adulteration levels between 0% and 100% lard fat (w/w). Raman spectroscopy coupled chemometrics was employed effectively for quantification of lard fat in butter fat samples with easy, robust, effective, low-cost and reliable application in the quality control of butter.